Współpraca na rzecz rodziny z perspektywy asystentów rodzin = Cooperation for the family from the perspective of family assistants - Hyży, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the article is to show cooperation with other entities in the opinion of family assistants. Family assistants also indicated the strengths and weaknesses of collaborations with various units as well as areas that would require improvement or ready solutions related to improving the collaboration of activities for the family.
Keywords: asystent rodziny; asystentura; współpraca; family assistant; assistantship; cooperation